2013
DOI: 10.1108/02683941311321169
|View full text |Cite
|
Sign up to set email alerts
|

Political skill and the job performance of bullies

Abstract: PurposeRecent studies suggest that 84 percent of employees are affected in some manner by workplace bullies. The current study aims to integrate theory from social information processing and political skill to explain how bullies can successfully navigate the social and political organizational environment and achieve higher ratings of performance.Design/methodology/approachA questionnaire, archival performance data, and social networks methodology were employed in a health services organization in order to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 50 publications
(73 reference statements)
6
30
0
Order By: Relevance
“…Kolodinsky et al (2007) found that, for politically skilled subordinates, the use of rationality tactics tends to result in supervisor perceptions of similarity to and liking of the subordinate, and, in turn, this also leads to higher supervisor-rated job performance. Treadway et al (2013b) found that the relationship between bullying and job performance is positive for politically skilled employees and negative for those politically unskilled, since politically skilled bullies can conceal their ultimate motives. Previous studies also found a mediating effect in reputation (Liu et al 2007;see Munyon et al 2014 for a metaanalysis).…”
Section: Kimuramentioning
confidence: 99%
“…Kolodinsky et al (2007) found that, for politically skilled subordinates, the use of rationality tactics tends to result in supervisor perceptions of similarity to and liking of the subordinate, and, in turn, this also leads to higher supervisor-rated job performance. Treadway et al (2013b) found that the relationship between bullying and job performance is positive for politically skilled employees and negative for those politically unskilled, since politically skilled bullies can conceal their ultimate motives. Previous studies also found a mediating effect in reputation (Liu et al 2007;see Munyon et al 2014 for a metaanalysis).…”
Section: Kimuramentioning
confidence: 99%
“…We argue that political skill will amplify the distancing effects of experienced powerlessness because employees who are high (vs. low) in political skill are particularly attuned to the consequences of power dynamics at work. Employees who are high (vs. low) in political skill place a high priority on understanding and attending to their social environment (Ferris et al., ; Treadway, Shaughnessy, Breland, Yang, & Reeves, ). This suggests that the effects of experienced powerlessness may be especially strong for politically skilled employees, because these employees are likely to view everyday interactions with their coworkers as manifestations of their powerlessness.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Due to their social competence and political skills, bullies are often able to strategically abuse coworkers and yet still be evaluated positively by their supervisors. 7 The term abrasive personality has been used to describe executives who exhibit competitive, dominating, and controlling tendencies that create friction in interpersonal relationships. 8 Such individuals seem to operate as though they were somehow privileged but are often unaware of their impact on others.…”
Section: The Individual Perspectivementioning
confidence: 99%